Iberian nautical heritage and its impact on the voyages of exploration - Fuertes-Manjón, Roberto (2022)
The important developments in nautical sciences that took place at the beginning of the sixteenth century were based on a foundation that had been established in the Middle Ages. One of the characteristics of these developments was the fact that there was cooperation between astronomers, cartographers and mariners from Portugal and Spain. Even though it was mostly the Portuguese who were the ones who conducted these developments, they had a common background within the Iberian Peninsula. Soeiro de Brito reminds us that the Portuguese contributions, such as the creation of the nautical guides of Munich and Évora, the development of methods to measure the latitude through astronomical observations, as well as the preparation of ephemerides and astronomical tables, put Portugal at the forefront of nautical development in Europe, by laying the foundation of modern navigation. It is also noteworthy to point out the relevance of two Spanish thinkers: Alfonso X the Wise and Raimundo Lulio. Furthermore, as an example of Iberian cooperation, Zacuto’s work stands out; the tables of his “Perpetual Almanac” were the basis of all the Portuguese tables published later. This study will investigate the common Iberian antecedents in the development of nautical sciences that led to the voyages of modern exploration.